WAWASAN AL-QUR’AN TENTANG GENDER (Sebuah Kajian dengan Pendekatan Tafsir Tematik) - Mosiba, Risna (Universitas Islam Negeri Alauddin Makassar, 2019)
Interpretation of al-Maraghi introduces principles of equality and gender justice. That the position of men and women is the same as the servant of God and the representative of God on earth (caliph fiy al-ardh). Basically, men and women are created from the same element. Later, both are involved in cosmic drama, when Adam and Eve are both guilty of causing it to be brought down to earth. Both have potential for earthly achievement, and both have the potential to achieve God's purpose in this world and in the hereafter.